Cinnamon essential oil synergizes with sodium hypochlorite to suppress VBNC formation in Escherichia coli O157:H7 by modulating the temporal expression of arcA/relA-associated stress regulators - Haoqing Zhao; Zongwei Bai; Jingfeng Zhang; Yamei Chen; Huiting Huang; Xiaoxuan Wang; Jiawen Sun; Lei Shi; Xiaoli Xu; Lichao Zhao (Food Microbiology, 2027)

Establishment of a degenerate primer-based multiplex qPCR method for sensitive detection of Gas-Producing Bacillus spp. in soy sauce - Huiting Huang; Jingfeng Zhang; Haoqing Zhao; Zhongsong Chen; Qian zou; Yiling Jin; Xiaobo Zeng; Lichao Zhao (Food Microbiology, 2026)

Trace Si-induced interfacial anchoring stabilizes Cu–CeO2 active sites for durable high-temperature reverse water–gas shift reaction - Linyu Zhang; Lulu Zhou; Liang Yuan; Haohao Feng; Jingfeng Han; Yongdong Chen (Chemical Engineering Journal, 2026)

Generation and application of monoclonal antibodies against CD4-1 and CD8α for characterizing T cell subsets in grass carp (Ctenopharyngodon idella) - Haokai Chen; Ming Geng; Kang Li; Zhichao Fang; Yating Zhu; Yuqing Yang; Shiqi Tang; Jingfeng Ding; Jiansong Zhang; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2026)

Experimental and numerical investigation of shear buckling behaviour of friction stir welded 6013-T6 aluminium H-shaped beams - Beibei Li; Yanjun Tong; Boshan Chen; Jingfeng Wang; Hongzhuang Yang; Yihe Guo; Bingbing Sun (Engineering Structures, 2026)

Toward environmentally stable magnesium metal anodes via Bi interphase engineering for rechargeable magnesium batteries - Sitong Liang; Yuhang Chen; Xiaojin Lian; Zhimeng Tang; Lu Zhang; Xinwei She; Baihua Qu; Jingfeng Wang (Chemical Engineering Journal, 2026)

A photothermal-enhanced nanozyme hydrogel with stimuli-responsive biofactor delivery for diabetic bone regeneration - Renxin Chen; Zouwei Li; Guang Shi; Haoran Lu; Mengyue Zhu; Zhuowen Hao; Zijian Wu; Luhao Li; Jiayao Chen; Zheyuan Zhang; Lanhong Guo; Tian Luan; et al. (Chemical Engineering Journal, 2026)

An elastic polyester-fish scale scaffold for sequential-release of biofactors to facilitate bone regeneration in postmenopausal osteoporosis with diabetes - Junwu Wang; Lanhong Guo; Wenjie Zhao; Shuai Chen; Yilong Huang; Tian Luan; Hao Chen; Peng Ma; Wen Min; Jinghuan Huang; Jingfeng Li (Chemical Engineering Journal, 2026)

Interfacial coordination and reinforcement mechanism in PBAT/Mica/MMT composites modified by Ca2+ and citric acid - Shunkai Yang; Jingfeng Huang; Xiangying Chen; Weiliang Tian (Applied Clay Science, 2026)

The rectal sac as a second liver for detoxification in the metamorphosing silkworm - Rongbing Chen; Jingfeng Yang; Shoulin Zhu; Erjun Ling; Qiuning Liu; Wuren Huang (Journal of Insect Physiology, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Fecal pollution source tracking at a marine bathing beach: A case study of Beihai Silver Beach - Hongxia Ming; Ziqi Chen; Tingting Shi; Zhongzhi Chen; Wenjing Pan; Jiannan Lin; Jie Su; Jingfeng Fan (Regional Studies in Marine Science, 2026)

Mechanical evaluation of high-performance fiber ropes: creep test, tensile response and joint behavior - Beibei Li; Yanjun Tong; Yuanqing Wang; Shaomin Chen; Zongyi Wang; Jingfeng Wang; Zhe Wang; Quanxi Ye (Ocean Engineering, 2026)

Synthesis of BMP wrist epitope-derived peptide functionalized bioink for 3D bioprinting of tissue-engineered bone constructs - Fei Huang; Guozhen Wei; Ying Zhang; Bing Wu; Yaoqing Chen; Yaoyu Qiu; Jingfeng Li; Gui Wu (Chemical Engineering Journal, 2026)

Dietary quercetin enhances T cell immunity and disease resistance in tilapia via modulating antioxidant and inflammatory responses - Haokai Chen; Jingfeng Ding; Yuqing Yang; Shiqi Tang; Qiqi Jiang; Yuying Zheng; Yating Zhu; Xiumei Wei; Jialong Yang (Aquaculture, 2026)

N-acetylcysteine enhances antioxidant capacity and anti-bacterial immunity of T cells in tilapia by regulating KEAP1-NRF2 axis - Kang Li; Shiqi Tang; Jingfeng Ding; Yuqing Yang; Haokai Chen; Qiqi Jiang; Xiumei Wei; Jialong Yang (Aquaculture, 2026)

Transformation mechanisms of dissolved organic matter in a full-scale initial rainwater treatment plant: An empirical study based on ultra-high-resolution mass spectrometry and microbial community analysis - Xiaowen Chen; Qiankun Liu; Shengjie Zhao; Jingwei Feng; Jingfeng Wang; Hao Yin; Daoyun Wu (Journal of Environmental Chemical Engineering, 2026)

Restraining grain growth and constructing defects in olivine-type silicate as high-performance cathode for rechargeable magnesium batteries - Jie Xu; Minjie Zhang; Rui Pu; Guangsheng Huang; Jingchao Zhang; Jianrong Zeng; Yanan Chen; Jingfeng Wang; Jili Yue; Fusheng Pan (Chemical Engineering Journal, 2026)

Large language model orchestrated workflow integrating retrieval-augmented generation and model context protocol tools for urban-scale simulation-based resilience assessment - Jingfeng Zhou; Jiying Chen; Meng Wang; Baihua Dong; Xiaochi Zhou (Building and Environment, 2026)

Spatiotemporal pattern of wheat harvest duration and its driving factors in the Huang-Huai-Hai plain of China - Renhai Zhong; Cong Chen; Guan Zhou; Xingguo Xiong; Qiyu Tian; Jingfeng Huang; Guangqiao Cao; Tao Lin (Computers and Electronics in Agriculture, 2026)

Leveraging sUAS-Sentinel-2 synergy for cross-scale mapping of canopy cover and aboveground biomass across Mongolia and Kazakhstan - Venkatesh Kolluru; Ranjeet John; Jiquan Chen; Geoffrey M. Henebry; Jingfeng Xiao; Rajat Shinde; Maira Kussainova; Ulgiichimeg Ganzorig (Remote Sensing of Environment, 2026)

Interfacial electronic reconstruction in Fe3O4-NiTe/NF heterostructures for efficient PET upcycling to high-value chemicals coupled with green hydrogen production - Peng Chen; Xinyuan Zhang; Chenyu Li; Yuqing Zhao; Xiaoqi Chen; Binni Wang; Jingfeng Wang (Chemical Engineering Journal, 2026)

Multi-satellite derived data reveals spatiotemporal dynamics of carbon-water coupling and its drivers in tropical ecosystems - Xiang Wang; Zheng Fu; Philippe Ciais; Josep Peñuelas; Jingfeng Xiao; Xing Li; Xiangzhong Luo; Chi Chen; Haoyu Xia; Tao Zhou; Paul C. Stoy; Julia K. Green; et al. (Remote Sensing of Environment, 2026)

Dual-mode regulation of cyclohexylamine biodegradation by dissolved oxygen: Metabolic trade-offs and community stability mechanisms - Cheng Qiu; Jingfeng Ding; Minwen Guo; Can Chen; Wenwu Zhang; Bin Yang; Yang Hou; Zhongjian Li (Journal of Water Process Engineering, 2026)

The trend and interannual variability in the global terrestrial evapotranspiration are respectively dominated by humid regions and drylands - Huiling Chen; Kun Zhang; Gaofeng Zhu; Lei Fan; Xin Li; Yunquan Wang; Xufeng Wang; Shasha Shang; Jia Jia; Yongtai Zhu; Jingfeng Xiao (Journal of Hydrology, 2026)

High-sensitivity, multi-modal triboelectric sensor derived from Kevlar for self-powered Morse code transmission and human-machine interaction - Tao Huang; Zhaoqing Lu; Fengfeng Jia; Ruixue Pang; Huimei Zhao; Pengbo Yang; Chunting Li; Jingfeng Chen; Li Hua (Chemical Engineering Journal, 2026)

Pulmonary sclerosing pneumocytoma with lymph node metastasis and high 18FDG uptake in PET/CT: a rare case report and literature review - Jingfeng Xu; Yilei Zhao; Qiuli Wu; Feng Chen (Journal of Zhejiang University-SCIENCE B, 2026)

Stronger Sensitivity of Plant Photosynthesis to Rising CO 2 in High Elevation Ecosystems - Yao Chen; Yangjian Zhang; Zhihua Liu; Shilong Piao; Jingfeng Xiao; Ashley Ballantyne; Philippe Ciais; Josep Peñuelas; Jie Gao; Yongwen Liu; Lin Jiang; Juntao Zhu; et al. (Ecology Letters, 2026)
The CO 2 ‐fertilisation effect (CFE) on vegetation productivity is the major driver of the enhanced land carbon sink in recent decades. CFE theoretically increases with elevation due to the higher sensitivity of carboxylation to an increase of CO 2 under lower CO 2 partial pressure, but the elevation‐dependent CFE pattern has been largely overlooked. By conducting a 6‐year CO 2 enrichment experiment (+100 ppm) in an alpine grassland, we show that elevated CO 2 increased gross primary production (GPP) by 25.5% ± 4.6%. Water availability and plant biomass allocation modulates CFE during different seasons. A global synthesis of 10 CO 2 enrichment experiments reveals that CFE increased with elevation. The satellite‐based EC‐LUE model also demonstrates a positive global elevation‐dependent CFE pattern, albeit substantially weaker than that from experimental observations. Current terrestrial biosphere models, however, could not represent the elevation‐dependent pattern, highlighting the need to improve the representations of plants' elevational physiological adaptation to rising CO 2 in models.

Enhanced T-cell activation and effector functions contribute to disease resistance in Streptococcus agalactiae-resistant tilapia - Ming Geng; Jingfeng Ding; Jun Xiao; Liting Chen; Jiansong Zhang; Kang Li; Jie Cheng; Yi Cao; Jialong Yang; Xiumei Wei (Aquaculture, 2026)

Environmental DNA reveals shift in phytoplankton community driven by sewage-derived eutrophication in coastal waters - Jie Su; Xuexin Wu; Tingting Shi; Shanshan Dong; Daoyang Shi; Hanjun Chen; Hongxia Ming; Jingfeng Fan (Marine Environmental Research, 2026)

Disentangling the climate–VPD–GPP Nexus: Global patterns and underlying drivers - Shanshan Chen; Jingfeng Xiao; Xing Li; Minchao Wu; Jie Yang (Global and Planetary Change, 2026)

Multidrug-resistant plasmid modulates ammonia oxidation efficiency in Nitrosomonas europaea through cyclic di-guanylate and acyl-homoserine lactones pathways - Jinrui Cao; Chen Zhao; Lin Bo; Xinxin He; Yuchao Liu; Shang Wang; Bin Xue; Jingfeng Wang (Bioresource Technology, 2026)

Ligation-mediated circuit-driven cascade amplification with high utilization rate of template for lncRNA MALAT1 detection in cancer mice tissues - Yuyan Huang; Fan Huang; Qianqian Du; Rui Yu; Jingfeng Lan; Junwei Luo; Hongli Chen; Huige Zhang (Analytica Chimica Acta, 2026)

Short-chain per/polyfluoroalkyl substances alternatives enhance horizontal gene transfer risks in nitrification systems under quaternary ammonium compounds antimicrobials co-stress despite lower acute toxicity than perfluorooctanoic acid - Hanyi Wang; Jingfeng Gao; Yingchao Cui; Yuxuan Wang; Yi Guo; Hao Chen (Water Research, 2025)

Transcriptome and metabolome analyses revealed mechanisms underlying vernalization-induced bolting in two contrasting genotypes of cabbage (Brassica oleracea var. capitata) - Huiju Yang; Jingfeng Hu; Mingwei Chen; Mei Lan; Jiangming He (Journal of Plant Biochemistry and Biotechnology, 2025)

Projecting city-scale energy performance under future weather scenarios through urban building energy modelling incorporating cluster archetypes - Jingfeng Zhou; Jiying Chen; Kaixuan Wang; Bingyu Xu; Xuhui Lin; Jiayi Yan; Meng Wang (Sustainable Cities and Society, 2025)

Multi-parameter input damage limit prediction for bare reinforced concrete frames using XGBoost - Chen Xiong; Yuchao Cao; Jingfeng Zheng; Linlin Xie; Liu Mei; Lixiao Li; Wujian Long (Soil Dynamics and Earthquake Engineering, 2025)

Impact of large-scale climate indices on total nitrogen concentrations in drinking water sources cannot be overlooked - Ning Li; Jingfeng Xiao; Zheng Zhang; Rui Bai; Jiayi Yong; Ziyu Ning; Miao Chen; Yaxiong Chen; Shuli Xin; Shengwu Xiong (Journal of Hydrology, 2025)

Explore the relationship between Bowen ratio and evapotranspiration in wetlands using the maximum entropy production model - Huaiwei Sun; Leying Fu; Weiguang Wang; Jie Xue; Jing Wang; Weihong Liao; Haicheng Li; Xunlai Sun; Yong Yang; Jingfeng Wang; Hong Zhang; Fulong Chen; et al. (Journal of Hydrology, 2025)

Preparation and characterization of glutamine/chito-oligosaccharide modified zein nanoparticles: Controlled release naringin and anti-diabetes - Yiyan Guo; Mingze Xu; Jiapeng Chen; Jingfeng Che; Wenqing Zhu; Yuxin Zheng; Wanting Huang; Wenjun Dai; Hong Chen; Limin Zhai; Li Zhang; Yan-Qing Guan (Food Chemistry, 2025)

Spider web-inspired ZIF@PPy conductive networks for efficient flow-electrode capacitive desalination of high-salinity antibiotic wastewater - Huachun Pan; Jingfeng Ding; Shuangwei Chen; Zhikang Li; Zhikan Yao; Chen Sun; Yang Hou; Zhongjian Li; Lecheng Lei; Bin Yang (Chemical Engineering Journal, 2025)

Net ecosystem exchange of CO2 and its driving mechanisms in an island forest nature reserve in southern China - Liangxu Wu; Shuya Xie; Xianglan Li; Pengpeng Tian; Zhe Xu; Yuting Huang; Jingfeng Xiao; Xintong Chen; Minghai Xu; Wei Chen; Houcai Cai (CATENA, 2025)

The impact of selenium fertilizer application on the yield, quality, and selenium accumulation characteristics of sweet potato - Huifeng Li; Yixuan Zhang; Yanqing Li; Yongmei Huang; Jingfeng Hua; Jie Yin; Dong Xiao; Tianyuan Chen (Acta Physiologiae Plantarum, 2025)

Removal and toxic intervention of polystyrene microplastics and nanoplastics by magnetic nano-Fe3O4 in spermatogonial GC-1 cells - Cheng Cheng; Yanfan Cui; Yujie Wang; Jingfeng Huang; Jiale Ma; Tao Luo; Wen Chen (Reproductive Toxicology, 2025)

Gradient multi-component interphase enabling highly reversible magnesium metal anode in fluorinated alkoxyborate-based electrolytes - Yuhang Chen; Yiming Zhang; Zhimeng Tang; Zhenyu Zhang; Le Tong; Xuemin Gan; Xing Shen; Guangsheng Huang; Qian Li; Baihua Qu; Fusheng Pan; Jingfeng Wang (Chemical Engineering Journal, 2025)

Hypertension Induces Cognitive Impairment and Alterations of Acetylcholine Receptor mRNA Expression in the Hippocampus and Cortex of Mice - Jingfeng Liu; Jianting Hou; Jianlin Wu; Wenjun Chen (NeuroMolecular Medicine, 2025)

Estimating carbon fluxes over North America using a physics-constrained deep learning model - Bin Fan; Hankui K. Zhang; Zhongbin B. Li; Jingfeng Xiao; Xianghong Che; Zhihua Liu; Gustau Camps-Valls; Jing M. Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

3D printing of scaffolds for articular cartilage/osteochondral regeneration: Design, performance, and applications - Luhao Li; Guang Shi; Zijian Wu; Zhenxin Cai; Junwu Wang; Zhuowen Hao; Renxin Chen; Zhenzhou Piao; Chao Chen; Jingfeng Li (Chemical Engineering Journal, 2025)

Assessment of spatial and temporal variability in fecal contamination patterns within urbanized bay shellfish growing area utilizing community-based microbial source tracking approaches - Jiannan Lin; Hongxia Ming; Dongwei Li; Jiajie Li; Zhongzhi Chen; Ziqi Chen; Tingting Shi; Jie Su; Jingfeng Fan (Environmental Monitoring and Assessment, 2025)

Decadal transport of trace elements in a cave system based on 16 years monitoring data: Implications for paleoclimate reconstruction - Xin Fu; Yan Yang; Jingyao Zhao; Yidong Li; Xiaomin Chen; Zhimao Ye; Mingyang Li; Jingfeng Lin; Yanzhi Xu (Applied Geochemistry, 2025)

Deciphering the interfacial electrochemistry of non-nucleophilic Mg(TFSI)2 as 4 V-class electrolyte for Mg batteries - Lu Zhang; Yuping Liu; Xiaolei Wang; Zhihong Cui; Chenlong Xiao; Changguo Chen; Jingfeng Wang; Guangsheng Huang; Dingfei Zhang; Fusheng Pan (Chemical Engineering Journal, 2025)

The interaction between banana polyphenols and starch improves the bioavailability of polyphenols after non-co-heating complexation - Yajuan Qin; Jingfeng Ran; Xiaoai Chen; Xuan Zhang; Yutong Zhang; Fei Xu; Kexue Zhu; Cuiping Yi; Yanjun Zhang (Food Hydrocolloids, 2025)

Machine learning enhanced bridge vulnerability quantification under rockfall hazards - Jingfeng Zhang; Yifan Jing; Jie Ma; Jiaxin Luo; Han Bao; Shizhi Chen (Engineering Geology, 2025)

Effects of combined stressors to TCDD and high temperature on HSP/CYPs signaling in the zebrafish embryos/larvae - Hongsong Chen; Hao Chen; Lian Hua; Yunqi Gao; Yuehua Yao; Yangfan Xu; Jingfeng Yang; Lingtian Xie; Yongju Luo; Ting Huang; Hongxing Chen; Xuguang Lin; et al. (Environmental Pollution, 2025)

Integrated Proteomics and Metabolomics Analyses Reveal Molecular Mechanism of Cardiac Resynchronization Therapy Against Cardiac Fibrosis and Ventricular Arrhythmias - Maoxiong Wu; Haiying Li; Jing Tan; Jingting Mai; Shaoxin Zheng; Qiong Qiu; Bingqing Deng; Hanlu Lv; Peiwei Wang; Jingfeng Wang; Yangxin Chen; Woliang Yuan (Cardiovascular Toxicology, 2025)

Heat Deficit for Vegetation Leaf Senescence and Its Key Accumulation Process and Determinants at Northern Middle and High Latitudes During 2001–2022 - Zhihui Yuan; Gang Bao; Fei Li; Jiquan Chen; Jingfeng Xiao; Qier Mu; Enliang Guo; Siqin Tong; Sainbuyan Bayarsaikhan (Global Ecology and Biogeography, 2025)
Aim Cold degree days (CDD) represent the heat deficit for vegetation leaf senescence in autumn and serve as a critical parameter in modelling leaf senescence. This study aimed to quantify the spatiotemporal patterns of CDD and its key accumulation processes and determinants. Location At northern middle and high latitudes (> 30° N). Period 2001–2022. Major Taxa Studied Vegetation. Methods We estimate CDD as the cumulative sum of the difference between the daily mean temperature and a threshold temperature (12.75°C) during the period from midsummer to the end of the growing season. To identify its crucial metric, we employ a combination of grey relational analysis, random forest model and partial correlation analysis. Results The average CDD increases linearly with latitude at a rate of 5.9°C‐days per degree. Higher latitudes exhibit larger CDD (> 300.0°C‐days), longer accumulation periods (> 70 days) and faster accumulation rates (> 6.0°C/day), whereas lower latitudes show smaller CDD ( 46% of the study area, especially at high latitudes and on the Tibetan Plateau. While climate warming generally reduces CDD, an increase in precipitation frequency can counteract this trend and shape the relationship between precipitation amount and CDD. The effects of radiation and wind speed on CDD were less pronounced than those of precipitation frequency, with wind exerting a positive (cooling) effect that increases CDD accumulation and radiation producing a negative (heating) effect that decreases CDD accumulation. Main Conclusions This study highlights the critical aspects of the CDD accumulation process and emphasises the importance of incorporating precipitation frequency into CDD‐based autumn phenology models across northern latitudes.

Unignorable environmental risks: Insight into differential responses between biofilm and plastisphere in sulfur autotrophic denitrification system upon exposure to quaternary ammonium compounds - Yuxuan Wang; Jingfeng Gao; Zhiqi Wang; Yifan Zhao; Hanyi Wang; Yi Guo; Yukun Yuan; Hao Chen (Journal of Hazardous Materials, 2025)

Estimating global transpiration from TROPOMI SIF with angular normalization and separation for sunlit and shaded leaves - Chen Zheng; Shaoqiang Wang; Jing M. Chen; Jingfeng Xiao; Jinghua Chen; Zhaoying Zhang; Giovanni Forzieri (Remote Sensing of Environment, 2025)

Importance of viewing angle: Hotspot effect improves the ability of satellites to track terrestrial photosynthesis - Haoran Liu; Jingfeng Xiao; Dalei Hao; Fa Li; Fujiang Ji; Min Chen (Remote Sensing of Environment, 2025)

TG-Net: A Physically Interpretable Deep Learning Forecasting Model for Thunderstorm Gusts - Yunqing Liu; Lu Yang; Mingxuan Chen; Jianwei Si; Maoyu Wang; Wenyuan Li; Jingfeng Xu (Journal of Meteorological Research, 2025)

In situ construction of ion/electron conductive components via lithiation strategy enhancing cycling capability and initial Coulombic efficiency of Si anode - Jingfeng Cao; Xiang Yan; Dan Li; Liuyi Hu; Tiansheng Chen; Weiwei Gao; Wenlong Song; Xinhui Xia; Yang Xia; Wenkui Zhang; Hui Huang (Chemical Engineering Journal, 2025)

Fluoride removal from coal mining water using novel polymeric aluminum modified activated carbon prepared through mechanochemical process - Yixiang Bao; Yonghui Qi; Qiao Li; Lei Wang; Zhiguo Cao; Jie Li; Min Wu; Jun Chen; Haiqin Zhang; Qiang Guo; Binbin Jiang; Jinkui Zhong; et al. (Journal of Environmental Sciences, 2024)

Degradation of low-molecular-weight fucoidans by human intestinal microbiota and their regulation effect on intestinal microbiota and metabolites during in vitro fermentation - Xiaona Sun; Yunning Yang; Chen Song; Chunqing Ai; Jingfeng Yang; Shuang Song (Food Bioscience, 2024)

Efficient extraction of rare earth elements from coal-series kaolin by combining alkali fusion and sulfamic acid leaching - Lingtao Zhu; Jingfeng He; Linghua Chen; Bin Yang (Process Safety and Environmental Protection, 2024)

Residual stress tests and predictive model of friction stir welded normal-strength aluminium alloy H-shaped sections - Beibei Li; Guoqiang Li; Jingfeng Wang; Boshan Chen; Yuanqing Wang; Yecheng Dai; Gang Dong (Engineering Structures, 2024)

Whatever does not kill them makes them stronger: Using quaternary ammonia antimicrobials to alleviate the inhibition of ammonia oxidation under perfluorooctanoic acid stress - Hanyi Wang; Jingfeng Gao; Hairong Ren; Yifan Zhao; Yuxuan Wang; Jiawen An; Hao Chen; Qian Wang (Water Research, 2024)

An automatic tracking method for fruit abscission of litchi using convolutional networks - Tong Huang; Jingfeng Guo; Long Yu; Houbin Chen; Zuanxian Su; Yueju Xue (Computers and Electronics in Agriculture, 2024)

Soil environmental anomalies dominate the responses of net ecosystem productivity to heatwaves in three Mongolian grasslands - Lu-Ping Qu; Gang Dong; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Jingyan Chen; Shicheng Jiang; Ochirbat Batkhishig; Tsegaye Gemechu Legesse; Xiaoping Xin; Changliang Shao (Science of The Total Environment, 2024)

A machine learning scheme for estimating fine-resolution grassland aboveground biomass over China with Sentinel-1/2 satellite images - Huaqiang Li; Fei Li; Jingfeng Xiao; Jiquan Chen; Kejian Lin; Gang Bao; Aijun Liu; Guo Wei (Remote Sensing of Environment, 2024)

Surface iso-transformation and floatability of calcite and fluorite - Xu Yang; Yubiao Li; Jingfeng Chen; Peng Chen; Shunxin Xie; Shaoxian Song (Minerals Engineering, 2024)

Natural pyrite and ascorbic acid co-enhance periodate activation for inactivation of antibiotic resistant bacteria and inhibition of resistance genes transmission: A green disinfection process dominated by singlet oxygen - Hao Chen; Jingfeng Gao; Qian Wang; Ying Liu; Xiaoyu Fu; Yi Guo; Hanyi Wang; Yuxuan Wang; Jiawen An (Journal of Hazardous Materials, 2024)

Hormesis and synergistic effects of disinfectants chloroxylenol and benzethonium chloride on highly efficient heterotrophic nitrification-aerobic denitrification functional strain: From performance to mechanism - Yi Guo; Jingfeng Gao; Yingchao Cui; Yifan Zhao; Biao Ma; Liqin Zeng; Hao Chen (Journal of Hazardous Materials, 2024)

Global convergence in terrestrial gross primary production response to atmospheric vapor pressure deficit - Chao Huang; Jingfeng Huang; Jingfeng Xiao; Xing Li; Hong S. He; Yu Liang; Fusheng Chen; Hanqin Tian (Science China Life Sciences, 2024)

Satellite-based monitoring of China's above-ground biomass carbon sink from 2015 to 2021 - Hongqian Fang; Lei Fan; Philippe Ciais; Jingfeng Xiao; Rasmus Fensholt; Jingming Chen; Frédéric Frappart; Weimin Ju; Shuli Niu; Xiangming Xiao; Wenping Yuan; Jiangzhou Xia; et al. (Agricultural and Forest Meteorology, 2024)

Examining the impact of common faults on chiller performance through experimental investigation and parameter sensitivity analysis - Zhanwei Wang; Penghua Xia; Sai Zhou; Lin Wang; Jingjing Guo; Xiuzhen Li; Jingfeng Shi; Jianxing Chen (Energy and Buildings, 2024)

A cell-free fluorescence biosensor based on allosteric transcription factor NalC for detection of pentachlorophenol - Shuting Chen; Chen Zhao; Xiaodan Kang; Xi Zhang; Bin Xue; Chenyu Li; Shang Wang; Xiaobo Yang; Chao Li; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Biotechnology Letters, 2024)

Removal of antibiotic resistant bacteria by the coupled system of ferrous ion activated peroxymonosulfate (PMS) and sodium percarbonate (SPC): Performance and mechanisms - Qian Wang; Jingfeng Gao; Hao Chen; Ying Liu; Xiaoyu Fu; Jiawen An; Hanyi Wang; Yuxuan Wang (Chemical Engineering Journal, 2024)

A Deep Learning Approach for Forecasting Thunderstorm Gusts in the Beijing-Tianjin-Hebei Region - Yunqing Liu; Lu Yang; Mingxuan Chen; Linye Song; Lei Han; Jingfeng Xu (Advances in Atmospheric Sciences, 2024)

Promoting the denitrification process by heavy metals in Liaohe Estuary sediment - Ming Hongxia; Zan Shuaijun; Liu Jiwen; Su Jie; Ren Kaijia; Lin Jiannan; Chen Quanrui; Shi Yinyin; Shi Tingting; Fan Jingfeng (Marine Pollution Bulletin, 2024)

Optimization of the electrode reaction kinetics of V2O5 via polyacrylonitrile intercalation for high-performance magnesium batteries - Rongrui Deng; Zhongting Wang; Shuangshuang Tan; Xueting Huang; Zhipeng Gao; Yongheng Fang; Chunfeng Chen; Ronghua Wang; Chaohe Xu; Guangsheng Huang; Jingfeng Wang; Fusheng Pan (Chemical Engineering Journal, 2024)

CRISPR/Cas12b assisted loop-mediated isothermal amplification for easy, rapid and sensitive quantification of chronic HBV DNA in one-pot - Haipo Xu; Gengping Lin; Ronghua Chen; Zhixiong Cai; Yupeng Sun; Xiaolong Zhang; Bixing Zhao; Yongyi Zeng; Jingfeng Liu; Xiaolong Liu (Analytica Chimica Acta, 2024)

Mechanisms and clinical application of Xuebijing injection, a traditional Chinese herbal medicine–a systematic review - Mengchi Chen; Wenbo Shu; Jingfeng Zhang; Hongyuan Huang; Jianghua Liu (Advances in Traditional Medicine, 2024)

Mechanisms on the removal of gram-negative/positive antibiotic resistant bacteria and inhibition of horizontal gene transfer by ferrate coupled with peroxydisulfate or peroxymonosulfate - Xiaoyu Fu; Jingfeng Gao; Qian Wang; Hao Chen; Ying Liu; Liqin Zeng; Yukun Yuan; Hongxin Xu (Journal of Hazardous Materials, 2024)

The synergistic effect of periodate/ferrate (VI) system on disinfection of antibiotic resistant bacteria and removal of antibiotic resistant genes: The dominance of Fe (IV)/Fe (V) - Hao Chen; Jingfeng Gao; Qian Wang; Ying Liu; Lei Wu; Xiaoyu Fu; Yi Guo; Hanyi Wang; Yuxuan Wang (Journal of Hazardous Materials, 2024)

Efficient peroxymonosulfate activation by nanoscale zerovalent iron for removal of sulfadiazine and sulfadiazine resistance bacteria: Sulfidated modification or not - Ying Liu; Jingfeng Gao; Qian Wang; Hao Chen; Yi Zhang; Xiaoyu Fu (Journal of Hazardous Materials, 2024)

Spatial distribution characteristics and interaction effects of DOM and microbial communities in kelp cultivation areas - Huiling Huang; Shuaijun Zan; Kuishuang Shao; Hanjun Chen; Jingfeng Fan (Science of The Total Environment, 2024)

High performance Pt/Nb2W3O14 catalyst for glycerol valorization to 1,3-propanediol - Jinghu Chen; Mingming Wang; Shude Zhang; Yaju Wang; Jingfeng Hua; Xiangtong Meng; Qineng Xia; Jieshan Qiu; Shaomin Liu (Chemical Engineering Journal, 2024)

Enhancing thermoelectric performance in GeTe through Ge enrichment regulation and AgCuTe alloying - Jingyi Lyu; Jingfeng Li; Wenwei Yang; Zhixing Chen; Zijie Ren; Zhanpeng Zhao; Shenghua Liu; Jing Shuai (Chemical Engineering Journal, 2024)

Erratum to: Bioinformatic analysis for potential biological processes and key targets of heart failure-related stroke - Chiyu Liu; Sixu Chen; Haifeng Zhang; Yangxin Chen; Qingyuan Gao; Zhiteng Chen; Zhaoyu Liu; Jingfeng Wang (Journal of Zhejiang University-SCIENCE B, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Dryland evapotranspiration from remote sensing solar-induced chlorophyll fluorescence: Constraining an optimal stomatal model within a two-source energy balance model - Jingyi Bu; Guojing Gan; Jiahao Chen; Yanxin Su; Mengjia Yuan; Yanchun Gao; Francisco Domingo; Ana López-Ballesteros; Mirco Migliavacca; Tarek S. El-Madany; Pierre Gentine; Jingfeng Xiao; et al. (Remote Sensing of Environment, 2024)

Establishing the global isoscape of leaf carbon in C3 plants through the integrations of remote sensing, carbon, geographic, and physiological information - Xiang Wang; Guo Chen; Joseph Awange; Yongze Song; Qi Wu; Xiaowei Li; Edmund February; Gustavo Saiz; Ralf Kiese; Xing Li; Jingfeng Xiao; Xiaoxiang Zhao; et al. (Remote Sensing of Environment, 2024)

Modeling transpiration using solar-induced chlorophyll fluorescence and photochemical reflectance index synergistically in a closed-canopy winter wheat ecosystem - Chen Zheng; Shaoqiang Wang; Jing M. Chen; Jingfeng Xiao; Jinghua Chen; Kai Zhu; Leigang Sun (Remote Sensing of Environment, 2024)

Cleaning and upgrading of low-rank coal using a novel rotary triboelectric separator with the polyvinyl chloride as friction medium - Bin Yang; Lingtao Zhu; Jingfeng He; Bin Liu; Shibo Huang; Hao Chen; Wenjie Tang (Fuel, 2024)

Multidrug-resistant plasmid RP4 inhibits the nitrogen removal capacity of ammonia-oxidizing archaea, ammonia-oxidizing bacteria, and comammox in activated sludge - Zhaohui Zhang; Lin Bo; Shang Wang; Chenyu Li; Xi Zhang; Bin Xue; Xiaobo Yang; Xinxin He; Zhiqiang Shen; Zhigang Qiu; Chen Zhao; Jingfeng Wang (Environmental Research, 2024)

Elevational variation in metabolic rate, feeding capacity and their associations in the Asiatic toad Bufo gargarizans - Yuechan Zhang; Song Tan; Jinzhong Fu; Jingfeng Chen (Journal of Thermal Biology, 2024)

The complexity of heatwaves impact on terrestrial ecosystem carbon fluxes: Factors, mechanisms and a multi-stage analytical approach - Lu-Ping Qu; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Gang Dong; Shi-Cheng Jiang; Ya-Lin Hu; Yi-Xuan Wang; Chang-Liang Shao (Environmental Research, 2024)

Effects of a multistrain probiotic on the growth, immune function and intestinal microbiota of the tongue sole Cynoglossus semilaevis - Zhongjie Zan; Kun Chen; Haoyi Wang; Zhuoran Han; Jingfeng Sun (Aquaculture, 2023)

Transcriptomic analysis of the hepatopancreas of white shrimp Penaeus vannamei following experimental infection with the Vibrio parahaemolyticus TJA114 - Xue Zhang; Zhuoran Han; Feng Chen; Xueliang Sun; Jingfeng Sun (Aquaculture, 2023)

Multidrug-resistant plasmid RP4 increases NO and N2O yields via the electron transport system in Nitrosomonas europaea ammonia oxidation - Jia Li; Chen Zhao; Chenyu Li; Bin Xue; Shang Wang; Xi Zhang; Xiaobo Yang; Zhiqiang Shen; Lin Bo; Xinxin He; Zhigang Qiu; Jingfeng Wang (Water Research, 2023)

Counting piglet suckling events using deep learning-based action density estimation - Haiming Gan; Jingfeng Guo; Kai Liu; Xinru Deng; Hui Zhou; Dehuan Luo; Shiyun Chen; Tomas Norton; Yueju Xue (Computers and Electronics in Agriculture, 2023)

Biomimetic single-atom nanozyme system for efficient inhibition of gastric cancer ascites via SO2 gas-enhanced nanocatalytic cancer therapy - Tao Chen; Xi Luo; Liwei Zhu; Jingfeng Xiang; Chuanfa Fang; Daoming Zhu; Guoxin Li; Yanhong Duo (Chemical Engineering Journal, 2023)

Study on integration of drying and separation for lignite by hot airflow gas–solid fluidized bed - Jingfeng He; Qingyao Yao; Mingming Zhang; Bin Yang; Lingtao Zhu; Hao Chen; Xin Zhang (Fuel, 2023)

Growth of grasses and forbs, nutrient concentration, and microbial activity in soil treated with microbeads - Jingfeng Wang; Xiao Guo; Janice Brahney; Zhenwei Xu; Yi Hu; Wenyi Sheng; Yanni Chen; Mingyan Li; Weihua Guo (Environmental Pollution, 2023)

Exploration of the metabolic flexibility of glycogen accumulating organisms through metatranscriptome analysis and metabolic characterization - Bin Zhao; Yanping Yang; Chen Zhao; Chunchun Zhang; Zhaohui Zhang; Liang Wang; Shang Wang; Jingfeng Wang (Journal of Environmental Sciences, 2023)

Surface modification to enhance the decarbonization performance of coal-series kaolin by triboelectric separation - Jingfeng He; Xin Zhang; Qiang Bai; Shibo Huang; Hao Chen; Chengjing Guo; Lingtao Zhu; Bin Yang (Applied Clay Science, 2023)

Revisiting the role of transpiration in the variation of ecosystem water use efficiency in China - Huaiwei Sun; Mengge Lu; Yong Yang; Jianing Chen; Jingfeng Wang; Dong Yan; Jie Xue; Wenxin Zhang (Agricultural and Forest Meteorology, 2023)

Docosahexaenoic acid inhibits pheromone-responsive-plasmid-mediated conjugative transfer of antibiotic resistance genes in Enterococcus faecalis - Hongrui Zhou; Xiaobo Yang; Yutong Yang; Yuanyuan Niu; Jing Li; Xinyue Fu; Shang Wang; Bin Xue; Chenyu Li; Chen Zhao; Xi Zhang; Zhiqiang Shen; et al. (Journal of Hazardous Materials, 2023)

Intermittent ultrasound retains cellulases unlock for enhanced cellulosic ethanol with high-porosity biochar for dye adsorption using desirable rice mutant straw - Zhen Hu; Qian Li; Yuanyuan Chen; Tianqi Li; Youmei Wang; Ran Zhang; Hao Peng; Hailang Wang; Yanting Wang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Accumulated soil moisture deficit better indicates the effect of soil water stress on light use efficiency of grasslands during drought years - Zhenyu Zhang; Yanlian Zhou; Weimin Ju; Jingming Chen; Jingfeng Xiao (Agricultural and Forest Meteorology, 2023)

Efficient recovery of valuable metals from waste printed circuit boards via ultrasound-enhanced flotation - Linghua Chen; Jingfeng He; Lingtao Zhu; Qingyao Yao; Youbang Sun; Chengjing Guo; Hao Chen; Bin Yang (Process Safety and Environmental Protection, 2023)

Experimental research on the performance and parameters sensitivity analysis of variable refrigerant flow system with common faults imposed in heating mode - Wei Gou; Zhaoting Ren; Huanxin Chen; Lu Xing; Zhenxin Zhou; Xingxiang Xia; Jingfeng Shi (Energy and Buildings, 2023)

A new pathway for anaerobic biotransformation of marine toxin domoic acid - Miaomiao Du; Yuan Jin; Jingfeng Fan; Shuaijun Zan; Chen Gu; Jing Wang (Environmental Science and Pollution Research, 2023)

A novel utilization of raw sepiolite: preparation of magnetic adsorbent directly based on sol–gel for adsorption of Pb(II) - Jiang Xu; Jingfeng He; Lingtao Zhu; Shulian Guo; Hao Chen (Environmental Science and Pollution Research, 2022)

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

Rapid detection method of Skeletonema pseudocostatum and preparation of test strip - Haoran Li; Kun Meng; Qiaojie Yu; Changping Chen; Jingfeng Chen; Jingli Li; Xinyi Wang; Yingzi Wang; Mingyang Li; Chuang Chen; Kefu Zhou (Environmental Science and Pollution Research, 2022)

Soil moisture regulates warming responses of autumn photosynthetic transition dates in subtropical forests - Yongshuo H. Fu; Xinxi Li; Shouzhi Chen; Zhaofei Wu; Jianrong Su; Xing Li; Shuaifeng Li; Jing Zhang; Jing Tang; Jingfeng Xiao (Global Change Biology, 2022)
Autumn phenology plays a key role in regulating the terrestrial carbon and water balance and their feedbacks to the climate. However, the mechanisms underlying autumn phenology are still poorly understood, especially in subtropical forests. In this study, we extracted the autumn photosynthetic transition dates (APTD) in subtropical China over the period 2003–2017 based on a global, fine‐resolution solar‐induced chlorophyll fluorescence (SIF) dataset (GOSIF) using four fitting methods, and then explored the temporal–spatial variations of APTD and its underlying mechanisms using partial correlation analysis and machine learning methods. We further predicted the APTD shifts under future climate warming conditions by applying process‐based and machine learning‐based models. We found that the APTD was significantly delayed, with an average rate of 7.7 days per decade, in subtropical China during 2003–2017. Both partial correlation analysis and machine learning methods revealed that soil moisture was the primary driver responsible for the APTD changes in southern subtropical monsoon evergreen forest (SEF) and middle subtropical evergreen forest (MEF), whereas solar radiation controlled the APTD variations in the northern evergreen‐broadleaf deciduous mixed forest (NMF). Combining the effects of temperature, soil moisture and radiation, we found a significantly delayed trend in APTD during the 2030–2100 period, but the trend amplitude (0.8 days per decade) was much weaker than that over 2003–2017. In addition, we found that machine learning methods outperformed process‐based models in projecting APTD. Our findings generate from different methods highlight that soil moisture is one of the key players in determining autumn photosynthetic phenological processes in subtropical forests. To comprehensively understand autumn phenological processes, in‐situ manipulative experiments are urgently needed to quantify the contributions of different environmental and physiological factors in regulating plants' response to ongoing climate change.

Monitoring and evaluation of antibiotic resistance genes in three rivers in northeast China - Chen Zhao; Chenyu Li; Xiaoming Wang; Zhuosong Cao; Chao Gao; Sicong Su; Bin Xue; Shang Wang; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Environmental Science and Pollution Research, 2022)

Expert consensus on organizing the multidisciplinary team (MDT) diagnosis and treatment of hepato-pancreato-biliary diseases in China - Binhao Zhang; Jian Zhou; Weifen Xie; Kaishan Tao; Shichun Lu; Xianglin Yuan; Lianxin Liu; Weilin Wang; Yilei Mao; Ping Bie; Jingfeng Liu; Xinyu Bi; et al. (Science China Life Sciences, 2022)

Decipher soil organic carbon dynamics and driving forces across China using machine learning - Huiwen Li; Yiping Wu; Shuguang Liu; Jingfeng Xiao; Wenzhi Zhao; Ji Chen; Georgii Alexandrov; Yue Cao (Global Change Biology, 2022)
The dynamics of soil organic carbon (SOC) play a critical role in modulating global warming. However, the long‐term spatiotemporal changes of SOC at large scale, and the impacts of driving forces remain unclear. In this study, we investigated the dynamics of SOC in different soil layers across China through the1980s to 2010s using a machine learning approach and quantified the impacts of the key factors based on factorial simulation experiments.Our results showed that the latest (2000–2014) SOC stock in the first meter soil (SOC 100 ) was 80.68 ± 3.49 Pg C, of which 42.6% was stored in the top 20 cm, sequestrating carbon with a rate of 30.80 ± 12.37 g C m −2 yr −1 since the 1980s. Our experiments focusing on the recent two periods (2000s and 2010s) revealed that climate change exerted the largest relative contributions to SOC dynamics in both layers and warming or drying can result in SOC loss. However, the influence of climate change weakened with soil depth, while the opposite for vegetation growth. Relationships between SOC and forest canopy height further confirmed this strengthened impact of vegetation with soil depth and highlighted the carbon sink function of deep soil in mature forest. Moreover, our estimates suggested that SOC dynamics in 71% of topsoil were controlled by climate change and its coupled influence with environmental variation (CE). Meanwhile, CE and the combined influence of climate change and vegetation growth dominated the SOC dynamics in 82.05% of the first meter soil. Additionally, the national cropland topsoil organic carbon increased with a rate of 23.6 ± 7.6 g C m −2 yr −1 since the 1980s, and the widely applied nitrogenous fertilizer was a key stimulus. Overall, our study extended the knowledge about the dynamics of SOC and deepened our understanding about the impacts of the primary factors.

Characterization of a novel Vibrio parahaemolyticus host-phage pair and antibacterial effect against the host - Chao Gao; Xiaobo Yang; Chen Zhao; Chenyu Li; Shang Wang; Xi Zhang; Bin Xue; Zhuosong Cao; Hongrui Zhou; Yutong Yang; Zhiqiang Shen; Pingfeng Yu; et al. (Archives of Virology, 2022)

Seasonal changes in GPP/SIF ratios and their climatic determinants across the Northern Hemisphere - Anping Chen; Jiafu Mao; Daniel Ricciuto; Dan Lu; Jingfeng Xiao; Xing Li; Peter E. Thornton; Alan K. Knapp (Global Change Biology, 2021)
Satellite‐derived sun‐induced chlorophyll fluorescence (SIF) has been increasingly used for estimating gross primary production (GPP). However, the relationship between SIF and GPP has not been well defined, impeding the translation of satellite observed SIF to GPP. Previous studies have generally assumed a linear relationship between SIF and GPP at daily and longer time scales, but support for this assumption is lacking. Here, we used the GPP/SIF ratio to investigate seasonal variations in the relationship between SIF and GPP over the Northern Hemisphere (NH). Based on multiple SIF products and MODIS and FLUXCOM GPP data, we found strong seasonal hump‐shaped patterns for the GPP/SIF ratio over northern latitudes, with higher values in the summer than in the spring or autumn. This hump‐shaped GPP/SIF seasonal variation was confirmed by examining different SIF products and was evident for most vegetation types except evergreen broadleaf forests. The seasonal amplitude of the GPP/SIF ratio decreased from the boreal/arctic region to drylands and the tropics. For most of the NH, the lowest GPP/SIF values occurred in October or September, while the maximum GPP/SIF values were evident in June and July. The most pronounced seasonal amplitude of GPP/SIF occurred in intermediate temperature and precipitation ranges. GPP/SIF was positively related to temperature in the early and late parts of the growing season, but not during the peak growing months. These shifting relationships between temperature and GPP/SIF across different months appeared to play a key role in the seasonal dynamics of GPP/SIF. Several mechanisms may explain the patterns we observed, and future research encompassing a broad range of climate and vegetation settings is needed to improve our understanding of the spatial and temporal relationships between SIF and GPP. Nonetheless, the strong seasonal variation in GPP/SIF we identified highlights the importance of incorporating this behavior into SIF‐based GPP estimations.

Bioinformatic analysis for potential biological processes and key targets of heart failure-related stroke - Chiyu Liu; Sixu Chen; Haifeng Zhang; Yangxin Chen; Qingyuan Gao; Zhiteng Chen; Zhaoyu Liu; Jingfeng Wang (Journal of Zhejiang University-SCIENCE B, 2021)

Metabolic cold adaptation in the Asiatic toad: intraspecific comparison along an altitudinal gradient - Song Tan; Ping Li; Zhongyi Yao; Gaohui Liu; Bisong Yue; Jinzhong Fu; Jingfeng Chen (Journal of Comparative Physiology B, 2021)

Spatio-temporal evolution and future scenario prediction of karst rocky desertification based on CA–Markov model - Fei Chen; Shijie Wang; Xiaoyong Bai; Fang Liu; Yichao Tian; Guangjie Luo; Qin Li; Jingfeng Wang; Luhua Wu; Yue Cao; Huiwen Li; Yuanhong Deng; et al. (Arabian Journal of Geosciences, 2021)

Potential of hotspot solar‐induced chlorophyll fluorescence for better tracking terrestrial photosynthesis - Dalei Hao; Ghassem R. Asrar; Yelu Zeng; Xi Yang; Xing Li; Jingfeng Xiao; Kaiyu Guan; Jianguang Wen; Qing Xiao; Joseph A. Berry; Min Chen (Global Change Biology, 2021)
Remote sensing of solar‐induced fluorescence (SIF) opens a new window for quantifying a key ecological variable, the terrestrial ecosystem gross primary production (GPP), because of the revealed strong SIF–GPP correlation. However, similar to many other remotely sensed metrics, SIF observations suffer from the sun‐sensor geometry effects, which may have important impacts on the SIF–GPP relationship but remain poorly understood. Here we used remotely sensed SIF, globally distributed tower GPP data, and a mechanistic model to provide a systematic analysis. Our results reveal that leaf physiology, canopy structure, and sun‐sensor geometries all affect the SIF–GPP relationship. In particular, we found that SIF observations in the sun‐tracking hotspot direction can be a better proxy of GPP due to the similar responses of light use efficiency and SIF escaping probability in the hotspot direction to the increasing incoming solar radiation. Such conclusions are supported by a variety of modeling simulations and satellite observations over various plant function types, at different time scales and with satellite observational modes. This study demonstrates the potential and advantage of normalizing SIF observations to the hotspot direction for better global GPP estimations. This study also demonstrates the great potentials of current and future spaceborne sun‐tracking satellite missions for a significant improvement in measuring and monitoring, at a wide range of spatial and temporal scales, the changes in terrestrial ecosystem GPP in response to anticipated changes in the Earth's environmental conditions.

Moisture availability mediates the relationship between terrestrial gross primary production and solar‐induced chlorophyll fluorescence: Insights from global‐scale variations - Anping Chen; Jiafu Mao; Daniel Ricciuto; Jingfeng Xiao; Christian Frankenberg; Xing Li; Peter E. Thornton; Lianhong Gu; Alan K. Knapp (Global Change Biology, 2021)
Effective use of solar‐induced chlorophyll fluorescence (SIF) to estimate and monitor gross primary production (GPP) in terrestrial ecosystems requires a comprehensive understanding and quantification of the relationship between SIF and GPP. To date, this understanding is incomplete and somewhat controversial in the literature. Here we derived the GPP/SIF ratio from multiple data sources as a diagnostic metric to explore its global‐scale patterns of spatial variation and potential climatic dependence. We found that the growing season GPP/SIF ratio varied substantially across global land surfaces, with the highest ratios consistently found in boreal regions. Spatial variation in GPP/SIF was strongly modulated by climate variables. The most striking pattern was a consistent decrease in GPP/SIF from cold‐and‐wet climates to hot‐and‐dry climates. We propose that the reduction in GPP/SIF with decreasing moisture availability may be related to stomatal responses to aridity. Furthermore, we show that GPP/SIF can be empirically modeled from climate variables using a machine learning (random forest) framework, which can improve the modeling of ecosystem production and quantify its uncertainty in global terrestrial biosphere models. Our results point to the need for targeted field and experimental studies to better understand the patterns observed and to improve the modeling of the relationship between SIF and GPP over broad scales.

Isolation and characterization of PoWRKY, an abiotic stress-related WRKY transcription factor from Polygonatum odoratum - Zhongping Wei; Jingfeng Ye; Zhiquan Zhou; Gang Chen; Fanjin Meng; Yifei Liu (Physiology and Molecular Biology of Plants, 2021)

Isolation and genomic characterization of a pathogenic Providencia rettgeri strain G0519 in turtle Trachemys scripta - Minghao Ye; Xiucai Hu; Aijun Lü; Jingfeng Sun; Chengxun Chen (Antonie van Leeuwenhoek, 2020)

Spatial distribution characteristics of bacterial community structure and gene abundance in sediments of the Bohai Sea - Quanrui Chen; Jingfeng Fan; Jie Su; Hongxia Ming; Zhihao Sun; Mengfei Li; Xiaohui Zhao; Yantao Wang; Yingxue Zhang; Huizhen Zhang; Yuan Jin; Xiaowan Ma; et al. (Acta Oceanologica Sinica, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Aberrant interhemispheric functional connectivity in first-episode, drug-naïve major depressive disorder - Hong Yang; Chengwei Wang; Gongjun Ji; Zhan Feng; Jingfeng Duan; Feng Chen; Xiaohong Joe Zhou; Yushu Shi; Haiyan Xie (Brain Imaging and Behavior, 2019)

An amino acid duplication/insertion in the Bm126 gene of Bombyx mori nucleopolyhedrovirus alters viral gene expression as shown by differential gene expression analysis - Jinshan Huang; Jingfeng Li; Chen Cheng; Xudong Tang; Xingjia Shen; Bifang Hao (Archives of Virology, 2019)

Condition dependence of advertisement calls in male African clawed frogs - Xiaocui Wang; Zhi-Jun Zhao; Yan Cao; Jianguo Cui; Yezhong Tang; Jingfeng Chen (Journal of Ethology, 2019)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Processes of coastal ecosystem carbon sequestration and approaches for increasing carbon sink - Yao Zhang; MeiXun Zhao; Qiu Cui; Wei Fan; JiaGuo Qi; Ying Chen; YongYu Zhang; KunShan Gao; JingFeng Fan; GuangYi Wang; ChongLing Yan; HaoLiang Lu; et al. (Science China Earth Sciences, 2017)

Biomarkers Associated with Ischemic Stroke in Diabetes Mellitus Patients - Shuisheng Yang; Jingfeng Zhao; Yuxiang Chen; Minxiang Lei (Cardiovascular Toxicology, 2016)

Detection of vegetation abundance change in the alpine tree line using multitemporal Landsat Thematic Mapper imagery - Yaoliang Chen; Dengsheng Lu; Geping Luo; Jingfeng Huang (International Journal of Remote Sensing, 2015)

Heavy metal flows in multi-resource utilization of high-alumina coal fly ash: a substance flow analysis - Chenjian Yu; Huiquan Li; Xiaoping Jia; Bo Chen; Qiang Li; Jingfeng Zhang (Clean Technologies and Environmental Policy, 2015)

Differences in sex reversion and growth between normal and neomale stock in half-smooth tongue sole, Cynoglossus semilaevis - Qiaomu Hu; Song-Lin Chen; Fengtao Gao; Yangzhen Li; Shanshan Liu; Feng Liu; Jingfeng Yang; Min Du (Aquaculture International, 2014)

Diversity and structure of bacterial communities in Fildes Peninsula, King George Island - Jingfeng Fan; Lili Li; Junli Han; Hongxia Ming; Jiangyu Li; Guangshui Na; Jiaying Chen (Polar Biology, 2013)

Functional study of immature dendritic cells co-transfected with IL-10 and TGF-beta 1 genes in vitro - Lihong Chen; Minglian Qiu; Wubing He; Aimin Huang; Jingfeng Liu (Molecular Biology Reports, 2012)

Etiology and epidemiology of viral diarrhea in children under the age of five hospitalized in Tianjin, China - Yabo Ouyang; Hui Ma; Min Jin; Xinwei Wang; Jingfeng Wang; Lu Xu; Shuxiang Lin; Zhiqiang Shen; Zhaoli Chen; Zhigang Qiu; Zhixian Gao; Lin Peng; et al. (Archives of Virology, 2012)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Overexpression of miR-22 reverses paclitaxel-induced chemoresistance through activation of PTEN signaling in p53-mutated colon cancer cells - Jian Li; Yangde Zhang; Jingfeng Zhao; Fangren Kong; Yuxiang Chen (Molecular and Cellular Biochemistry, 2011)

Genetic linkage maps of barfin flounder (Verasper moseri) and spotted halibut (Verasper variegatus) based on AFLP and microsatellite markers - Hongyu Ma; Songlin Chen; Jingfeng Yang; Siqing Chen; Hanwen Liu (Molecular Biology Reports, 2011)

Isolation of sex-specific AFLP markers in Spotted Halibut (Verasper variegatus) - Hongyu Ma; Songlin Chen; Jingfeng Yang; Xiangshan Ji; Siqing Chen; Yongsheng Tian; Jinzhen Bi (Environmental Biology of Fishes, 2010)

Sub‐pixel reflectance unmixing in estimating vegetation water content and dry biomass of corn and soybeans cropland using normalized difference water index (NDWI) from satellites - Jingfeng Huang; Daoyi Chen; M. H. Cosh (International Journal of Remote Sensing, 2009)